2019
DOI: 10.5194/bg-16-4429-2019
|View full text |Cite
|
Sign up to set email alerts
|

Weathering rates in Swedish forest soils

Abstract: Abstract. Soil and water acidification was internationally recognised as a severe environmental problem in the late 1960s. The interest in establishing “critical loads” led to a peak in weathering research in the 1980s and 1990s, since base cation weathering is the long-term counterbalance to acidification pressure. Assessments of weathering rates and associated uncertainties have recently become an area of renewed research interest, this time due to demand for forest residues to provide renewable bioenergy. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 88 publications
1
8
0
Order By: Relevance
“…The annual weathering rates calculated by ForSAFE are well within the range presented in Akselsson et al [46], which compiles weathering rates calculated by seven different methods on comparable soils in Sweden. The current annual average weathering calculated in this study, at 0.35 keq•ha −1 •year −1 , is similar to an earlier estimate at 0.33 keq•ha −1 •year −1 using the steady state model PROFILE [19].…”
Section: Discussionsupporting
confidence: 80%
“…The annual weathering rates calculated by ForSAFE are well within the range presented in Akselsson et al [46], which compiles weathering rates calculated by seven different methods on comparable soils in Sweden. The current annual average weathering calculated in this study, at 0.35 keq•ha −1 •year −1 , is similar to an earlier estimate at 0.33 keq•ha −1 •year −1 using the steady state model PROFILE [19].…”
Section: Discussionsupporting
confidence: 80%
“…The subaerial biofilms at this interface today remain stressful environments (Gorbushina, 2007), but ionising radiation levels are now much lower due to thickening of the Earth's atmosphere. Biomarker evidence (Brocks et al, 1999) in rocks formed 200 million years (Myr), before the increase in atmospheric oxygen, suggests that oxygen was already being produced before 2.5 Ga. Oxygenic photosynthesis by cyanobacteria is a likely source of this oxygen but there is evidence that stromatolites were abundant between 3.4 and 2.4 Ga, prior to the advent of cyanobacteria and oxygenic photosynthesis (Allen, 2016), and that Archaean microbial mats of protocyanobacteria switched between photolithoautotrophic and photoorganoheterotrophic metabolism prior to the evolution of cyanobacteria with simultaneous, constitutive expression of genes allowing both types of metabolism. It is also likely that phototrophy based on purple retinal pigments similar to the chromoprotein bacteriorhodopsin, discovered in halophilic Archaea, may have dominated prior to the development of photosynthesis (DasSarma and Schweiterman, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Models greatly improve our ability to quantify weathering rates and how they change over time. Akselsson et al (2019) present an extensive review of methods for estimating weathering rates in forest soils. These range from mass-balance budget calculations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Callesen et al, 2016;Brantley et al, 2017), the discrepancy in weathering rates between the two methods would be reduced since PROFILE predicted higher weathering rates with increasing depth. Furthermore, although biological processes are represented in PROFILE, the model fails to capture biological feedback mechanisms in their entirety, in particular feedbacks generated by plant uptake and mycorrhiza (Fin-lay et al, 2009(Fin-lay et al, , 2019Sverdrup, 2009;Smits and Wallander, 2017;Akselsson et al, 2019;Rosenstock et al, 2019a).…”
Section: Weathering In a Base Cation Budget Perspectivementioning
confidence: 99%
“…Because it is a mechanistic model, its strength is its trans-parency, while its main weakness is the difficulty in setting values of model parameters and input variables to which it may have high sensitivity. Akselsson et al (2019) concluded that the most important way to reduce uncertainties in modelled weathering rates is to reduce input data uncertainties, e.g. regarding soil texture, although there is still a need to improve process descriptions of biological weathering and weathering brakes (e.g.…”
Section: Introductionmentioning
confidence: 99%